Enzymatic depolymerization of industrial lignins by laccase‐mediator systems in 1, 4‐dioxane/water. (8th March 2020) - Dillies, Justine; Vivien, Céline; Chevalier, Mickael; Rulence, Alexandre; Châtaigné, Gabrielle; Flahaut, Christophe; Senez, Vincent; Froidevaux, Renato
Abstract: Lignin is the second most abundant polymer after cellulose in lignocellulosic biomass. Its aromatic composition and recalcitrant nature make its valorization a major challenge for obtaining low molecular weight aromatics compounds with high value‐added from the enzymatic depolymerization of industrial lignins. The oxidation reaction of lignin polymer using laccases alone remains inefficient. Therefore, researches are focused on the use of a laccase‐mediator system (LMS) to facilitate enzymatic depolymerization. Until today, the LMS system was studied using water‐soluble lignin only (commercial lignins, modified lignins, or lignin model compounds). This work reports a study of three LMS systems to depolymerize the three major industrial lignins (organosolv lignin, Kraft lignin, and sodium lignosulfonate). We show that an enzymatic depolymerization of these lignins can be achieved by LMS using laccase from Trametes versicolor, 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt as mediator and a cosolvent (25% of 1, 4‐dioxane) to enhance the solubilization of lignins. Abstract : LMS for lignin depolymerization in 1, 4‐dioxane/water.